GE_GERICHTE P/2303/2022 vom 2. Februar 2022 - GE Cour de justice (2022)
SOUPÇON;MINORITÉ(ÂGE);COMPÉTENCE FONCTIONNELLE;INDICE;NOUVEAU MOYEN DE PREUVE;CONSULTATION DU DOSSIER | CPP.40; CPP.221; CPP.225